The Role of Podcasts in the 2024 Political Campaigns Reviewed through the Perspective of Symbolic Interaction Theory - Habibah, Tiara Maulinda; Revolusi, Prabu (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The 2024 Indonesian election is a significant political event, with social media playing a crucial role in campaign communication and message conveying. Candidates and political parties use social media to garner support and mobilize voters, making campaigns more measurable and targeted. The Unpacking Indonesia Podcast, hosted by Zulfan Lindan, is a political discussion platform that invites various figures and analysts to discuss current issues in detail. The podcast features diverse speakers such as Hasan Nasbi, M. Qodari, Adi Prayitno, and Eros Djarot. Symbolic interaction theory, introduced by George Herbert Mead and Herbert Blumer, emphasizes the importance of symbols and social interaction in shaping social meaning and reality. In the context of the podcast "Unpacking Indonesia," political symbols are created and modified through discussions between Zulfan and his sources. These statements, analyses, and views become symbols that listeners interpret, influencing their perceptions and actions. Social media, podcasts, and symbolic interaction theory are interrelated in shaping social and political realities in the digital era. Political podcasts have become effective social media in disseminating political information and discourse to the public, offering in-depth discussions on complex issues and featuring a variety of sources from academics to activists. Interaction and involvement with listeners through question-and-answer sessions or panel discussions make podcasts more interesting and interactive. Political podcasters often work independently of mainstream media, presenting alternative, more critical perspectives. By spreading political discourse through podcasts, they can influence public opinion and garner support for various political issues, making them an important platform in the media ecosystem.